Huququl Insan Wajhatu Nadhara Islamiyyah - Asmuni Thahir (Millah: Journal of Religious Studies, 2001)
The Islamic ideas of human rights came long with the born of Islam its self. But the brilliant ideas about it were started to elaborate and to develope by Moslem intellectual in the end of forties together with the born of higher spirit to come back to Qur'anic concept regarding "istikhlaf al-ilahi" namely the duty from Allah for human being to make the world prosper, facing to the "al qanun at thabi'i" concept or natural law which be basis for international declaration of human right. Then, on 1980's non-party Moslem intellectual again point out the human rights by referencing to the Syatibi concept about "maqashid al syari 'ah" but still basis of "al istikhlaf" anf "taklif" concept. In fact, identity conflict among the global life during 3decades later caused the making of several laws and declaration of human rights in Islam from some sides, whether individual, group, institute or even state. All pointed out the unity and the perfection of Islamic teaching.